Economic considerations for smallholder cattle milk and meat production and marketing. II. Production related aspects - Brokken, R.F.; Williams, Timothy O. (International Livestock Centre for Africa, 1991)
Identifies constraints to and opportunities for improved meat and milk production in Africa; w., particularly emphasis on the increase of the quantity and quality of feed, improved nutrition, genetic improvement, animal health delivery system and disease control; and finally on risk adoption which is a constraint to increased productivity in the process of technology development or policy formulation.